KAJIAN LITERATUR ARSITEKTUR MENGENAI HOME INDUSTRY - Muallif, Muhammad Dzaki Al; Kusumaningayu, Intan; Rolalisasi, Andarita (Jurnal Teknik Gradien, 2024)
Ceramic crafts in Malang City itself are one of the attractions that can be developed to advance Malang City, especially in the tourism sector and also in the economic sector. There is one specific area in the form of a village area in Malang City which is also known as a center for pottery and ceramic crafts. This village is also known as the Dinoyo Ceramic Tourism Village which is located on Jl. M.T. Haryono, Lowokwaru District, Malang City. This area initially developed in 1957, this area has also experienced ups and downs, but it still manages to exist until now. The majority of the surrounding community is developing a home industry-based ceramic and pottery industry. Currently, there are approximately 31 ceramic craftsmen who are still active and live in the area. However, the sustainability of this area as a center for ceramics and pottery is starting to be threatened, this is due to the loss of the area's identity and lack of innovation, so if this continues, it is not impossible that this area could eventually be eroded.